Measurement of four-jet production in proton-proton collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2209 authors) (2014)
Measurements of the differential cross sections for the production of exactly four jets in proton-proton collisions are presented as a function of the transverse momentum pt and pseudorapidity eta, together with the correlations in azimuthal angle and the pt balance among the jets. The data sample was collected in 2010 at a center-of-mass energy of 7 TeV with the CMS detector at the LHC, with an integrated luminosity of 36 inverse picobarns. The cross section for a final state with a pair of hard jets with pt > 50 GeV and another pair with pt > 20 GeV within abs(eta) < 4.7 is measured to be sigma = 330 +- 5 (stat.) +- 45 (syst.) nb. It is found that fixed-order matrix element calculations including parton showers describe the measured differential cross sections in some regions of phase space only, and that adding contributions from double parton scattering brings the Monte Carlo predictions closer to the data.